Bernoulli and Riccati fractional differential equations can be solved analytically by using conformable derivatives - Salim S.Mahmood, KamaranJ.Hamad,SarwarA.Hamad,Dlvan Omar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Bernoulli and Riccati fractional differential equations are solved analytically using conformable derivatives in this paper. And To demonstrate the proposed solution, numerical examples of each equation are given.